Pusat Kegiatan Mahasiswa Universitas Riau Dengan Pendekatan Arsitektur Tropis - Hadi Gusmara; Pedia Aldy; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Riau University has many student organizations. But there is no adequate facility and place to do some student activities. Therefore, it is required a place to do those activities which is called Student Center. Student Center can be a place to develop their interest, aspiration and creativity. Besides, it can facilitate them in doing some student activities. This building applies tropical architecture approach by Georg Lippsmeier. The principles of this approach are in the form of the building orientation, the ventilation, the use of sun protection, the vegetation and the roof shape. It also applies the concept of dynamic activity. It takes the students’ character who always active, enthusiasm and energetic in the organizational activity. This concept is applied to the architectural aspect by applying dynamic principles, namely: transformation, starting and ending point, direction and flow.Keywords: Student Center, Tropical Architecture, Dynamic Activity